Is sarcopenia an associated factor of increased administration of specific medications in patients with heart failure? A systematic review and meta-analysis - Saied, Schabnam; Prokopidis, Konstantinos; Adenaya, Adeoye; Isanejad, Masoud; Sankaranarayanan, Rajiv (Frontiers in Cardiovascular Medicine, 2024)
Background There is controversy in relation to commonly used drugs in heart failure (HF) and their impact on muscle function. The aim of this study was to evaluate the odds of receiving specific medications often used in clinical practice by patients with HF and sarcopenia vs. without sarcopenia. Methods A systematic literature search of cohort studies via databases (PubMed, Web of Science, Scopus, and Cochrane Library) was conducted from inception until March 2023. To determine if sarcopenia is linked to a higher number of specific HF-related medications, a meta-analysis using a random-effects model was used to calculate the pooled effects. Results Our main analyses showed no significant association of sarcopenia with administration of higher HF-related medication count vs. those without sarcopenia. Those with lower appendicular lean mass (ALM) had significantly lower odds of receiving angiotensin converting enzyme inhibitors (ACE-Is)/angiotensin receptor blockers (ARBs) (OR: 0.68, 95%CI 0.50–0.90, I2 = 12%, P < 0.01) vs. patients with higher ALM for which age could be an important confounder based on meta-regression. No statistically significant differences were found in relation to B-blockers OR: 0.84, 95%CI 0.63–1.12, I2 = 7%, P = 0.24) and loop diuretics (OR: 1.19, 95%CI 0.87–1.63, I2 = 0%, P = 0.27). Regarding handgrip strength, gait speed, and short physical performance battery, our narrative synthesis found mixed results. Conclusion This systematic review and meta-analysis did not find a relationship of specific medication count in sarcopenia vs. without sarcopenia in patients with HF, although increased odds of ACE-I/ARB was shown in those with higher ALM. Systematic Review Registration PROSPERO (CRD42023411137).